Principle of Accounting and Performance of Secondary School Student in Enugu State, Nigeria - Agbeyinka, Ibrahim Yinka (International Journal of Social Science and Religion (IJSSR), 2025)
Since organized life evolved, accounting has been practiced. Financial accounting principles are designed to prepare students for studying financial accounting in general, in spite of the obvious need for principle of accounting in such a growing economy like ours, students seem to be shying ways from it opinions have widely varied as to the causes. Following this, this study aims at examining principle of accounting and performance of secondary school student in Enugu State, Nigeria. The participants in this study were residents of Enugu South Local Government Area, Nigeria. The sample size was calculated using the population figure, from which a total of 200 responders were chosen. The research selected for this study was descriptive research design and sample technique of random sampling was used. The results based on respondents' responses show that computational abilities for principle of account is a problem for students. The study recommends that it is impossible to overstate the importance of having qualified accounting teachers. Secondary schools should provide more training for accounting teachers.  Additionally, the government ought to support accounting teachers by offering scholarships and other incentives to make their training easier.